Trajectories and Depressive Symptoms During the Perinatal Period: A Longitudinal Population-Based Study in China - Bao, Ciqing; Jin, Dongzhen; Sun, Shiyu; Xu, Ling; Wang, Chaoyue; Tang, Weina; Zhang, Wenmiao; Bao, Yin; Xu, Dongwu; Zhou, Siyao; Yu, Xin; Zhao, Ke (Frontiers in Psychiatry, 2022)
Most women in the perinatal period face sleep issues, which can affect their mental health. Only a few studies have focused on sleep trajectories and depressive symptoms of women during the perinatal period in China. This study aims to explore the development trajectory of sleep quality by classifying pregnant women according to the changes in their sleep quality during pregnancy and postpartum, and investigate the correlation between different sleep quality trajectory groups and depressive symptoms. The Pittsburgh Sleep Quality Index (PSQI) was used to assess the sleep quality and the Edinburgh Postnatal Depression Scale (EPDS) was used to assess the symptoms of depression. Participants (n=412) completed the assessment of sleep quality, depressive symptoms, and some sociodemographic and obstetric data at 36 weeks of gestation, 1 week after delivery, and 6 weeks after delivery. The group-based trajectory model(GBTM) was used to complete the trajectory classification, and logistic regression was used to analyze the predictive factors of postpartum depressive symptoms. Four different sleep quality trajectories were determined: “Stable-good” group, “Worsening” group, “Improving” group and “Stable-poor” group. The results demonstrate that poor sleep trajectories, social support and parenting experience during the perinatal period are related to postpartum depression. Screening for prenatal sleep problems is crucial for identifying the onset of perinatal depressive symptoms.